Strategi Optimalisasi Penggunaan SIMRS untuk Meningkatkan Kinerja Rumah Sakit - Sri Hajijah Purba; Khairunnisa Khairunnisa; Chindy Khairani; Nur Wanny (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
In the era of rapid technological advancement, the health sector has undergone significant transformation, especially with the implementation of Information and Communication Technology (ICT) systems. One of the important innovations in this field is the Hospital Management Information System (SIMRS). The research method used in this study is a literature study or literature review, which is a research approach that utilizes existing sources of information, such as books, scientific articles, journals, research reports, and other sources relevant to the topic being studied. The results of this study indicate that One of the main strategies for optimization is to ensure comprehensive training for all hospital staff, from administrative personnel to health care providers. Effective use of SIMRS requires an understanding of its various functions. Implementation and optimization of the Hospital Management Information System (SIMRS) is one of the very important strategic steps in efforts to improve hospital performance. SIMRS integrates various operational, administrative, and clinical functions in one platform that allows hospitals to improve efficiency, quality of patient care, and the effectiveness of overall hospital management. However, its implementation also has challenges, such as high implementation costs, difficulty in integrating existing systems, and resistance from staff who are accustomed to manual systems.